Assessment of hydrologic connectivity in an ungauged wetland with InSAR observations. (24th January 2018) - Jaramillo, Fernando; Brown, Ian; Castellazzi, Pascal; Espinosa, Luisa; Guittard, Alice; Hong, Sang-Hoon; Rivera-Monroy, Victor H; Wdowinski, Shimon
Abstract: The Ciénaga Grande de Santa Marta (CGSM) is one of the world's most productive tropical wetlands and one that has witnessed some of the greatest recorded dieback of mangroves. Human-driven loss of hydrologic connectivity by roads, artificial channels and water flow regulation appears to be the reason behind mangrove mortality in this ungauged wetland. In this study, we determined the CGSM's current state of hydrologic connectivity by combining a remote sensing technique, termed as Wetland Interferometric Synthetic Aperture Radar (InSAR), with a hydrologic study of river water discharge. For this research, we processed 29 ALOS-PALSAR acquisitions taken during the period 2007–2011 and generated 66 interferograms that provide information on relative surface water level changes. We found that change in water discharge upstream on the main tributary of the CGSM could explain at most 17% of the variance of the change in water level in the CGSM. Fresh water inputs into the wetland were identified only when the mean daily water discharge in the river exceeded 700 m 3 s −1, which corresponds to only 30% of the days during the period. The interferogram analysis also revealed that artificial channels within the wetland serve as barriers to water flow and contribute to the overall loss in hydrologic connectivity. We recommend increasing fresh water inputs from the Magdalena River by reducing water regulation of fresh water from the river and improving connectivity on either side of the artificial channels crossing the CGSM. This study emphasizes the potential of the application of wetland InSAR to determine hydrologic connectivity in wetlands that are completely or poorly ungauged and to define the necessary guidelines for wetland hydrologic restoration.